Students seeking to inspire in South Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Two students from the University of the North in South Africa, describe their participation in projects, through which they are supporting rural development in their home areas, and improving their own farming practices. One of the students describes her work with women who are prevented from working together by their fears of witchcraft.